Si Bijak Nombor An Interactive Learning Application That Emphasize Number for Special Education Students - NUR NABILAH HANANI BINTI MOHD YUSOF; NORAZIAHTULHIDAYU BINTI KAMARUDIN (Applied Information Technology And Computer Science, 2026)
"Si Bijak Nombor" is an interactive application aimed at improving numerical literacy in primary school children aged 8 to 10, particularly special education students. Many children, especially those in special education, struggle with conventional teaching methods, which they often find unengaging and difficult to follow. This leads to a lack of interest in learning numbers and delays in acquiring basic mathematical skills. The application is developed using the Multimedia Development Life Cycle (MDLC), which emphasizes a structured process in the design and integration of multimedia elements. It is suitable for use in educational settings such as primary schools, special education programs, and also as a home learning aid. "Si Bijak Nombor" aims to spark student's interest in mathematics and enhance their understanding of basic mathematical concepts.